Análise e comparação de frameworks de persistência - Neves, Édina Maria das (2012)
Due to differences between the Object Oriented model, used in software development, and the model of Relational Databases, emerged techniques object-relational mapping(ORM) that allow better communication between the two models. However, there are several specifications and frameworks of object-relational mapping techniques that implement ORM, so it is necessary to decide which implementation to use when developing software. This study aims to analyze andcompare some of the existing solutions for the Java platform. We chose the persistence frameworks: Spring, Hibernate, TopLink and DataNucleus. Comparisons were made based on information collected during the making of the theoretical framework and criteria for analysis of general and specific frameworks of object-relational mapping in the literature on the subject and tested in an application using resources available in the Guidance object. At the end is a summary of the main benefits and limitations of each framework analyzed in this study.